The The Influence of Leadership, Organizational Culture, and Compensation on Employee Performance at PT. Siraj Badawi Cukup Rupiah (SBCR) - Bagus Hardiansyah; Tedy Maulana; Ade Solahudin; Sunimah Sunimah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Employee performance is an important factor in the success of the company. Leadership, organizational culture, and compensation are variables that are expected to be explained in this study related to employee performance. Data processing in this study was carried out using SPSS 25, using quantitative methods. Employees of PT Siraj Badawi Cucup Rupiah were selected as the sample through the use of simple random sampling. Participants in this survey were randomly selected from a population of 151 employees; 110 respondents were randomly selected to fill out the questionnaire using the Slovin formula. The results of the study can be concluded if leadership, organizational culture, and compensation have a positive and significant effect on employee performance, and leadership, organizational culture, and compensation together affect employee performance.